Деякі особливості поховального інвентаря єгипетської жриці Несмут - Тарасенко, М.О. (Археологія, 2024)
У статті досліджено поховальний інвентар єгипетської жриці XXI династії на ім’я Несмут. Її поховання було виявлено 1891 р. у т. зв. «другому тайнику» в Дейр ель-Бахрі (Баб ель-Гусус, комплект A.48). Зроблено висновок про можливість вторинного використаття у складі її інвентаря предметів іншої жриці, яка також мала ім’я Несмут і, можливо, була її родичкою. The subject of this paper is the analysis of funerary assemblage of Nesmut, the Egyptian priestess of the 21st Dynasty (her titles are “Mistress of the House, Chantress of Amun, king of the gods”). The burial of Nesmut was discovered in 1891 in the so-called “Second Cache” at Deir al-Bahri, also known as Bāb el-Gusūs (set no. A.48). Inventory that was discovered on the mummy: leather mummy braces, three “napkins”, linen gloves, shale heart scarab, and wax images of the sons of Horus. Inventory that was found near or inside of the coffin: two shabti-boxes, shabtis. Nesmut’s mummy cover is located in the Museum of Antiquities in Cairo (Cairo CG 6007). Her coffin is currently stored in the Odesa Archaeological Museum (OAM) of the National Academy of Sciences of Ukraine (inv. no. 71695). It was part of the so-called Lot VI presented to Russian Empire by Egyptian government in 1893. In 1895, the coffin of Nesmut was sent from Odesa to the Archaeological Museum of St. Volodymyr Kyiv University. In 1959 the coffin of Nesmut was among other objects that were transferred from the State Republican Historical Museum in Kyiv to the OAM. The lid of the coffin with inv. no. OAM 71695 differs in design style from the trunk and has an earlier dating. Structurally, the lid has retained traces of technological processing and fitting the trunk of the later coffin of its namesake. Accordingly, there were two Nesmuts, whose funerary objects were discovered in Bāb el-Gusūs. The burial of Nesmut (II) corresponds to the set no. A.48 by Daressy and it is linked with the coffin trunk no. OAM 71695. Separate objects from Nesmut’s (I) grave goods were adapted for later burials: the lid of her inner coffin was used for the Odesa coffin of Nesmut (II), and the lid of the outer coffin might have been adapted for an anonymous burial from Bāb el-Gusūs set no. A.54 (Swiss lot IX, Neuchâtel, Musée d’Ethnographie, inv. no. Eg. 184) on which the name “Nesmut” preserved in one segment of the lid. The burial of Nesmut was also equipped with two different types of shabtis. It is possible that like the lid of the coffin, part of the shabtis was “usurped” by Nesmut (II) and previously belonged to the burial of her namesake and probably relative, Nesmut (I). It is quite probable, that they were reused and adopted for the burial of new owner together with the shabti-box, since the two of them were found in the set no. A.48. This may prove that during the 21st Dynasty, not only large objects, but also small items of grave goods could be reused.